Maternal Stress and Offspring Lifelong Labor Market Outcomes - Vincenzo Atella; Edoardo di Porto; Joanna Kopinska; Maarten Lindeboom (Tinbergen Institute, 2020)
This paper examines the effects of in-utero exposure to stress on lifelong labor market outcomes. We exploit a unique natural experiment that involved randomly placed Nazi raids on municipalities in Italy during WWII. We use administrative data on the universe of private sector workers in Italy and link this data to unique historical data with detailed information about war casualties and Nazi raids across space (Municipality) and time. We find that prenatal stress exposure leads to lower wage earnings when workers start their career, and that this effect persists until retirement. The earnings penalty is in large part due to the type of job that people hold and interruptions in their working career due to unemployment. We further show that workers exposed to in-utero stress face larger earnings reductions after job loss due to mass layoffs. This earnings loss deepens their relative disadvantage over time.
Keywords: I1; J1; 330; Early-life; Stress; Life-long earnings; mass layoff; dynamic complementarities